The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s40273-018-0709-3
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Patiromer and Spironolactone Therapy in Heart Failure Patients with Hyperkalemia

Abstract: Background and ObjectiveCertain patients with heart failure (HF) are unable to tolerate spironolactone therapy due to hyperkalemia. Patiromer is a novel agent used to treat hyperkalemia and has been shown to be efficacious, safe, and well-tolerated. The potential clinical outcomes and economic value of using patiromer and spironolactone in patients with HF unable to otherwise tolerate spironolactone due to hyperkalemia are unclear. The objective of this analysis was to model the potential pharmacoeconomic valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Although such data are limited, costeffectiveness analysis from the US payer perspective found that the benefits of adding patiromer to treatment in patients with HF and hyperkalemia outweighed the incremental total costs, with lower hospitalization costs, improved survival, and increased quality of life. 97 Sodium Polystyrene Sulfonate. Sodium polystyrene sulfonate is a polymeric cation- exchange resin that binds K þ ions in exchange for sodium ions in the distal colon.…”
Section: Potassium Bindersmentioning
confidence: 99%
“…Although such data are limited, costeffectiveness analysis from the US payer perspective found that the benefits of adding patiromer to treatment in patients with HF and hyperkalemia outweighed the incremental total costs, with lower hospitalization costs, improved survival, and increased quality of life. 97 Sodium Polystyrene Sulfonate. Sodium polystyrene sulfonate is a polymeric cation- exchange resin that binds K þ ions in exchange for sodium ions in the distal colon.…”
Section: Potassium Bindersmentioning
confidence: 99%
“…Le groupe traité par patiromer montre non seulement une réduction significative de lhyperkaliémie par rapport au groupe placebo mais cette diminution se traduit cliniquement par un moins grand nombre darrêt dun traitement par inhibiteur du RAS 13 . Toutefois, lengouement pour cette nouvelle molécule peut être pondéré par au moins deux aspects : son coût de 375,38 pour 30 sachets (quoique certains défendent léconomie engendrée par une qualité de vie et de survie sur un plus grand nombre de patients traités par inhibiteur du RAS, argument qui reste à démontrer par une étude prospective) et surtout par le fait quelle na pas été comparée directement au standard actuel, une résine échangeuse d ions classique 15 . CONCLUSION Aussi, au vu de la faible fréquence de la nécrose colique, prouver une plus grande tolérance du patiromer sur une résine classique nécessiterait une étude face à face de ces deux molécules avec plusieurs dizaines de milliers de participants à enrôler, ce qui ne se fera probablement jamais.…”
Section: Discussionunclassified
“…A single, industry-sponsored analysis found patiromer had an incremental cost-effectiveness ratio of $52,700/QALY. [48] This study made strong assumptions regarding the overall clinical impact of patiromer based on the OPAL-HK trial, a single-arm study of patients with hyperkalemia and chronic kidney disease (including non-heart failure patients) that demonstrated patiromer's potassium-lowering effect. [49] With limited effectiveness data, the economic value of patiromer remains uncertain.…”
Section: Cost-effectiveness Of Current Heart Failure Therapiesmentioning
confidence: 99%